Keeping metaphor in mind: training therapists in metaphor-enhanced cognitive behaviour therapy. (9th July 2018) - Mathieson, Fiona; Jordan, Jennifer; Bennett-Levy, James; Stubbe, Maria
Abstract: Over the last decade, there has been increasing interest in the use of metaphor in cognitive behaviour therapy. However, to date, there has been only very limited research on the use of metaphor in CBT sessions, and no studies which have examined how to train therapists in this skill. The present study is the first in the literature to explore how we might train therapists in metaphor-enhanced CBT. Twelve therapists attended two half-day training workshops, 2 weeks apart. Details of the content of the training workshop are provided. The therapists rated the workshop quality and provided structured self-report ratings and reflections on their ongoing application of learning over a 3-month period which were compared with pre-training ratings. Therapists reported significantly increased awareness of metaphors, with increased confidence in responding intentionally to client metaphors and bringing them into shared conceptualizations. In addition, there were significant increases in reported time spent elaborating on client metaphors, and use of metaphors when conceptualizing with clients. Barriers and solutions to application of learning are discussed.